Geochemical Characteristics and Origin of Tight Gas in Member Two of the Upper Triassic Xujiahe Formation in Western Sichuan Depression, Sichuan Basin, SW China - Wu, Xiaoqi; Liu, Quanyou; Chen, Yingbin; Yang, Jun; Zeng, Huasheng; Li, Huaji (Frontiers in Earth Science, 2022)
Natural gas in the tight sandstone reservoirs in Member 2 of the Upper Triassic Xujiahe Formation in the Western Sichuan Depression of the Sichuan Basin has complex geochemical characteristics, and the origin and source of the tight gas are revealed based on the geochemical analysis and comparison in this study. The tight gas has the dryness coefficient of 0.950-0.994, which is positively correlated with the CH4 content. The gaseous alkanes display positive carbon isotopic series, with the δ13C1 and δ13C2 values ranging from -35.6‰ to -30.3‰ and from -29.1‰ to -21‰, respectively, and the δD1 values range from -176‰ to -155‰. Genetic identification based on the carbon and hydrogen isotopic compositions indicates that, a small amount of the tight gas is typically coal-derived gas, whereas most of the tight gas samples have experienced mixing by oil-associated gas. Geochemical comparisons suggest that the tight gas displays distinct differences with the typical oil-associated gas in Member 4 of the Middle Triassic Leikoupo Formation in the Chuanxi gas field and the typical coal-derived gas in Member 5 of Xujiahe Formation in the Xinchang gas field. It is also apparently different from the typical coal-derived gas in Member 2 of Xujiahe Formation in both Zhongba and Qiongxi gas fields. Among the tight gas in Member 2 of the Xujiahe Formation from the Western Sichuan Depression, the coal-derived gas is generated mainly by the humic mudstone in the Upper Triassic Ma’antang and Xiaotangzi formations, with assistance of the humic mudstone in Member 2 of the Xujiahe Formation, whereas the oil-associated gas is derived from the sapropelic limestone in the Ma’antang Formation.